Biomimetic Ultra‐Black Sponge Derived from Loofah and Co‐MOF for Long‐Term Solar‐Powered Vapor Generation and Desalination. Issue 5 (5th May 2021) - Wang, Hongqiang; Zhang, Chen; Zhang, Zhihua; Zhou, Bin; Shen, Jun; Du, Ai
Abstract : Solar‐Powered Vapor Generation In article number 2000817, Ai Du and co‐workers fabricated an ultra‐black sponge with the typical antireflection structure inspired by the crest‐ridge structures in the black scales of Bitis rhinoceros and used it for solar‐powered vapor generation and desalination. The ultra‐black sponge has excellent solar‐thermal conversion and solar‐powered vapor generation performances, combined with its low‐cost and durability, making it possible to provide sufficient drinking water in homes and industry.